Complete genome anatomy of the emerging potato pathogen Dickeya solani type strain IPO 2222T. Issue 1 (December 2016) - Khayi, Slimane; Blin, Pauline; Chong, Teik; Chan, Kok-Gan; Faure, Denis
Abstract Several species of the genusDickeya provoke soft rot and blackleg diseases on a wide range of plants and crops.Dickeya solani has been identified as the causative agent of diseases outbreaks on potato culture in Europe for the last decade. Here, we report the complete genome of theD. solani IPO 2222T . Using PacBio and Illumina technologies, a unique circular chromosome of 4, 919, 833 bp was assembled. The G + C content reaches 56% and the genomic sequence contains 4, 059 predicted proteins. The ANI values calculated forD. solani IPO 2222T vs. other availableD. solani genomes was over 99.9% indicating a high genetic homogeneity withinD. solani species.